2013
DOI: 10.4172/2157-7048.1000161
|View full text |Cite
|
Sign up to set email alerts
|

Response Surface Methodology for Adsorption of Fluoride Ion Using Nanoparticle of Zero Valent Iron from Aqueous Solution

Abstract: This study is removal of fluoride ion from aqueous solution by nano zero valent iron (nZVI). Effects of the factor variables (temperature, nZVI dose and pH) and their interactions on adsorption of fluoride ion were investigated by response surface methodology (RSM) based on Box-Behnken design (BBD). Optimized values of temperature, nZVI dose and pH for fluoride sorption were found as 313K, 0.5 g, and 4, respectively. The effect of initial fluoride concentration on the adsorption amount was investigated by a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The results obtained from XRD showed that the presence of nZVI in a biofilm on nZVI−C−A beads and a few other 2θ peaks at 35.68°correspond to the iron oxide layer on nZVI, bacterial cells, and calcium alginate beads. 41 The XRD patterns for nZVI−C−A beads and a biofilm on nZVI−C−A beads after interaction with Cr(VI) (Figure 4C,D where nZVI particles were acting as reductants, which is an agreement with the previous literature. 43 Figure 5 shows SEM images of nZVI−C−A beads and a biofilm on the nZVI−C−A beads.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 90%
“…The results obtained from XRD showed that the presence of nZVI in a biofilm on nZVI−C−A beads and a few other 2θ peaks at 35.68°correspond to the iron oxide layer on nZVI, bacterial cells, and calcium alginate beads. 41 The XRD patterns for nZVI−C−A beads and a biofilm on nZVI−C−A beads after interaction with Cr(VI) (Figure 4C,D where nZVI particles were acting as reductants, which is an agreement with the previous literature. 43 Figure 5 shows SEM images of nZVI−C−A beads and a biofilm on the nZVI−C−A beads.…”
Section: Industrial and Engineering Chemistry Researchsupporting
confidence: 90%
“…Fluoride is considered a potentially dangerous species for human health, and the maximum permissible concentration of fluoride in drinking water has been set at 1.5 mg/l (Organization 1993;Directive 1998). The continuous exposure to high fluoride levels in drinking water affects the metabolism of calcium, potassium, and phosphorus in the human body leading to several health problems (Fakhri & Adami 2013). Health issues such as dental, skeletal, and non-skeletal forms of fluorosis affect over 60 million people in India (Deepthi et al 2021), and about 120 million people are in high-risk areas for fluoride exposure (Podgorski et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nano-scale iron particles represent a new generation of environmental remediation technologies that could provide cost-effective solutions to some of the most challenging environmental clean-up problems [17]. Nano-scale iron particles have large surface areas and high surface reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays zero valent iron nanoparticles have been identified as the potential adsorbent for removal of chlorinated solvents, organochlorine pesticides, polychlorinated biphenyls, organic dyes, and inorganic pollutants, heavy metal ions, tetracycline due to their higher surface to volume ratio, higher reactivity, small size and high adsorption capacity [19]. In a recent study, nZVI was prepared and applied to remove excessive fluoride from water [17]. The removal rate of fluoride reached 84 % in 35 min with nZVI dosage of 0.6 g/l and pH 4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation